MANCO CAPAC’S RELIGION, THE MORNING STAR - coello, Oscar (2011)
This article shows some texts where Inca Garcilaso describes the religion of the Incasin the Royal Commentaries; and in which, in his own way, the fictional narrator seeksto match with it, the essential truths of the Western Christian religion. Previously,our article contextualizes, with regard to the topic, the literary discourse of thislofty writer belonging to the Hispanic-American Renaissance. The original versionof this paper was read in the Jesuit University Antonio Ruiz de Montoya on theoccasion of the four-hundredth anniversary of the zenith book of the Inca.